Mineralogical Characteristics and Beneficiation Experimental Study on Polytype Pyrrhotite in Kafang Deposit, Yunnan Province - Rong ZHAO; Baoxu SONG; Jiuran PU; Jie WU; Mingbo CHEN; Xiaoyan SUN (Kuangchan zonghe liyong)
With the increase of pyrrhotite content in Kafang copper-tungsten deposit, how to reduce the effects of pyrrhotite on the beneficiation process of copper and tungsten has become a difficult problem. The main types of pyrrhotite in Kafang deposit are identified, including monoclinic pyrrhotite, which is easy to magnetize and float, and hexagonal pyrrhotite, which has great magnetic changes due to the fluctuation of iron content. Beneficiation experiments show that using combined technological process of flotation and magnetic separation, a sulfur concentrate assaying over 32% of sulfur content, mainly recovering monoclinic pyrrhotite pyrrhotite, was obtained, and magnetic gangue minerals with a yield of about 23%, mainly included by hexagonal pyrrhotite and hedenbergite, were discarded to tailings. The interference of pyrrhotite to the flotation process of copper and tungsten is reduced, and the related methods can provide references for similar mining enterprises at home and abroad.